Global stability detection in the asynchronous distributed computations - Naimi, M. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
A simple algorithm for detecting global stability in asynchronous distributed computations is presented. it is based on observation of the outgoing channels, using a single token which acts as observer. No vector is necessary (in the transmission of the token on the ring), and this algorithm does not require the first-in/first-out (FIFO) property for the communication channels.< >